Gold-catalyzed one-pot synthesis of 1,3-disubstituted allenes from benzaldehydes and terminal alkynes - Lustosa, Danilo Machado; Clemens, Simon; Rudolph, Matthias; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2019)
A new and facile one-pot synthesis of 1,3-disubstituted allenes, using cheap and readily available terminal alkynes, benzaldehyde derivatives and morpholine, was developed. A small library of 20 allenes demonstrates a broad applicability, with yields up to 86%. Isotopic-labelling and cross-over experiments strongly indicate that our reaction proceeds via a two-step A3-coupling followed by a 1,5-hydrogen shift process.